Impact of diet and environmental enrichment management in stereotyped behaviours: a case study in tayra Eira barbara - Beltran, Ana [UNESP]; Bernal, Daniel (European Assoc Zoos & Aquaria - Eaza, 2024)
Holistic approaches have been implemented to minimise stress expressed as stereotypies associated with low welfare conditions, which can arise from a range of factors such as frustration, adaptation attempts and neurological problems. Such behaviour was identified in a tayra housed in the facilities of the Santacruz Zoo (San Antonio de Tequendama, Colombia), for which a five domains model of animal welfare evaluation was carried out. This allowed the creation of a corrective plan that included the provision of a hiding place, nutritional management and environmental enrichment. Prior to the corrective plan, the tayra displayed the following behaviours within a 12-hour period: 28.8% stereotypies, 28.8% inactivity, 25.3% aggressive behaviours, 8.2% feeding-related behaviours and 7.7% locomotion activities. After implementing the corrective measures, the behaviours shifted to 16.2% stereotypies, 15.2% inactivity, 28.0% feeding-related behaviours and 8.0% locomotion activities. In conclusion, evaluating and managing the five domains is an essential practice for zoos and can lead to significant improvement in an animal's welfare status.
Keywords: animal welfare; five domains; mustelids; nutrition; stereotypies